Types and Presentation of Refractive Error among Individuals Aged 0–30 Years: Hospital-Based Cross-Sectional Study, Yemen. (5th July 2021) - Mohammed Dhaiban, Tawfik Saleh; Ummer, Femina Purakaloth; Khudadad, Hanan; Veettil, Shajitha Thekke
Abstract : Background . Refractive errors are the most common cause of visual impairment worldwide. Its proportion varied among societies and is considered as a public health challenge. Symptoms and signs associated with refractive errors are the most worrisome and common presentations in the general practice in eye clinics. Aim . The goal of this study was to determine the types and presentations of refractive error among the 0–30-year-old Yemeni population to aid early identification, diagnosis, referral, and treatment. Methodology . A cross-sectional study including 1, 500 out-patients aged from 0 to 30 years attending the ophthalmology clinic in Sanaa, Yemen (between 2012 and 2015). All patients underwent visual acuity examination, autorefractometer, and anterior and posterior segment examination and were grouped according to type, that is, myopia, hyperopia, and astigmatism. Results . Hyperopia was the most common single diagnosis (53.3%) followed by myopia (33.3%). Astigmatism was uncommon as a single diagnosis (13.4%) but commonly associated with hyperopia or myopia. Myopia was more common in males (42.9%) than in females (25%). Hyperopia was more in females (62.5%) than in males (42.9%). Age groups most affected by refractive errors were 13–18 years (27.7%), 19–24 years (24.8%), and 25–30 years (24.6%), respectively. Decreased vision (53%) was a common presentation in myopia and astigmatism (41.5%) and less in hyperopia (39.6%). Headache was common in astigmatism (56%), hyperopia (28.8%), and myopia (17.8%). Muscle imbalance, namely, exotropia (27.2%), is mainly found in myopia and esotropia (24.3%) in hyperopia. Conclusions . In addition to decreased vision, our patients with refractive errors mostly complain of headaches with clear variations with age and type of refractive error. Early identification and proper categorization of refractive errors by age, gender, and other demographics by general physicians in primary care can better deduce and make useful referrals to eye specialists.